2008
DOI: 10.1007/s11142-008-9081-4
|View full text |Cite
|
Sign up to set email alerts
|

Propping through related party transactions

Abstract: Based on a sample of Chinese listed firms from 1998 through 2002, this paper documents that listed firms prop up earnings by using abnormal related sales to their controlling owners. Such related sales propping is more prevalent among state-owned firms and in regions with weaker economic institutions. We also find that these abnormal related sales are not entirely accrual-based but can be cashbased as well, and they serve as a substitute rather than complement to accruals management for meeting earnings target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
492
0
26

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 692 publications
(544 citation statements)
references
References 38 publications
26
492
0
26
Order By: Relevance
“…The results indicate that related-party transactions enjoy a more positive CSR effect on long-term M&A performance than those with non-related party transactions. Our findings are contradicted by some studies, which concluded CSR leads to a "Resource Hollowing" effect [9,[51][52][53][54]. However, our findings are consistent with studies which concluded CSR brings about an "Efficiency Enhancing" effect [11][12][13].…”
Section: Effects Of Related-party Transactions On Csr-performance Linsupporting
confidence: 50%
See 1 more Smart Citation
“…The results indicate that related-party transactions enjoy a more positive CSR effect on long-term M&A performance than those with non-related party transactions. Our findings are contradicted by some studies, which concluded CSR leads to a "Resource Hollowing" effect [9,[51][52][53][54]. However, our findings are consistent with studies which concluded CSR brings about an "Efficiency Enhancing" effect [11][12][13].…”
Section: Effects Of Related-party Transactions On Csr-performance Linsupporting
confidence: 50%
“…Significant evidence exists to show that controlling shareholders are more likely to tunnel through related-party transactions than to prop up a firm [51][52][53]. With respect to M&A activities, there are also negative effects of related-party transactions.…”
Section: Csr Related-party Transactions and Long-term Manda Performancementioning
confidence: 99%
“…the ownership structure and corporate control. In particular, many studies focus on the relationship between ownership structure (Jian & Tak, 2010;Kun, 2005;Munir, 2010;Zengquan, Sun, & Wang, 2004), the role played by the stock market (Gordon et al, 2004;Lo, Wong, & Firth, 2010;Yeh, Shu, & Su, 2012) and the quality and relevance of RPTs in corporate life. Cernat (2004) argues that CG represents not only a crucial difference between varieties of capitalism but is also a major factor in determining their economic performance.…”
Section: Literature Review Of Rptsmentioning
confidence: 99%
“…Business groups can overcome institutional voids and market failures by relying on the group's internal capital market and talent pool, by building intangible assets such as strong group reputation and brand names, and by accumulating expertise and knowledge from different affiliates operating in various locations (Belenzon and Berkovitz, 2010;Chang and Hong, 2000;Gopalan et al, 2007;Jian and Wong, 2010;Keister, 1998Keister, , 2001Khanna and Palepu, 2000;Khanna and Rivkin, 2001;Mahmood and Mitchell, 2004). The literature points to the performance advantages that emerging market business groups enjoy compared with other firms (e.g., Mahmood et al, 2011;Manikandan and Ramachandran, 2014).…”
Section: Business Groups In Chinamentioning
confidence: 99%